2018
DOI: 10.23922/jarc.2017-026
|View full text |Cite
|
Sign up to set email alerts
|

Absorptive anti-adhesion barrier for the prevention of bowel obstruction after laparoscopic colorectal cancer surgery

Abstract: Abstract:Objectives: The protective efficacy of an absorptive adhesion prevention product (Seprafilm ) against bowel obstruction (BO) during open surgery was demonstrated in a large-scale randomized controlled clinical trial in Europe and America. However, the efficacy of Seprafilm against BO in laparoscopic surgery remains uncertain. The objective of this study was to clarify the protective efficacy of Seprafilm against BO after laparoscopic surgery for colorectal cancer. Methods: From 2009 to 2016, 1328 lap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…With the increase in minimally invasive colorectal surgery performed today, our sub-analysis of laparoscopic operations is relevant. Our results support previous reports that Sepra lm® can reduce intestinal obstruction after laparoscopic surgery, (17) where the reduced trauma from laparoscopic surgery has been shown to prevent adhesion formation in itself (22). By removing this confounder, it gives us con dence that Sepra lm® will continue to remain relevant.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…With the increase in minimally invasive colorectal surgery performed today, our sub-analysis of laparoscopic operations is relevant. Our results support previous reports that Sepra lm® can reduce intestinal obstruction after laparoscopic surgery, (17) where the reduced trauma from laparoscopic surgery has been shown to prevent adhesion formation in itself (22). By removing this confounder, it gives us con dence that Sepra lm® will continue to remain relevant.…”
Section: Discussionsupporting
confidence: 89%
“…NR: Not ReportedOf these studies, eight studies focused solely on colorectal resections(11,(14)(15)(16)(17)(18)(19)(20), with four laparoscopic(16)(17)(18)(19)(20) and four open studies(11,14,15,19) (Table2).…”
mentioning
confidence: 99%
“…In a study of patients with FAP refusing surgery, invasive colorectal cancer was not observed during a median follow-up of 5.1 years and there were no complications, suggesting that endoscopic management might prevent cancer development in patients with FAP [ 10 , 16 ]. On the other hand, partial colectomy with subsequent regular surveillance colonoscopy is recommended in patients with Lynch syndrome and colorectal cancer, although the appropriate interval of surveillance colonoscopy after partial colectomy remains unclear [ 17 ]. However, colonoscopy performed in 6-month intervals was occasionally insufficient to detect endoscopically resectable tumors in some patients with high risk Lynch syndrome.…”
Section: Discussionmentioning
confidence: 99%